Genetic isolation of a blood pressure quantitative trait locus on chromosome 2 in the spontaneously hypertensive rat - Pravenec, M; Zídek, V; Musilová, A; Vorlícek, J; Kren, V; St Lezin, E; Kurtz, T W (Journal of hypertension, 2001)
OBJECTIVES: Total genome scans of genetically segregating populations derived from the spontaneously hypertensive rat (SHR) and other rat models of hypertension have suggested the presence of quantitative trait loci (QTL) regulating blood pressure and cardiac mass on multiple chromosomes, including chromosome 2. The objective of the current study was to directly test for the presence of a blood pressure QTL on rat chromosome 2. DESIGN: A new congenic strain was derived by replacing a segment of chromosome 2 in the SHR between D2Rat171 and D2Arb24 with the corresponding chromosome segment from the normotensive Brown Norway rat. Arterial pressures were directly monitored in conscious rats by radiotelemetry. RESULTS: We found that the SHR congenic strain (SHR-2) carrying a segment of chromosome 2 from the Brown Norway rat had significantly lower systolic and diastolic blood pressures than the SHR progenitor strain. The attenuation of hypertension in the SHR-2 congenic strain versus the SHR progenitor strain was accompanied by significant amelioration of cardiac hypertrophy. CONCLUSIONS: These findings demonstrate that gene(s) with major effects on blood pressure exist in the differential segment of chromosome 2 trapped within the new SHR.BN congenic strain.
Keywords: Quantitative Trait, Heritable; Rats; genotyp; krevní tlak; chromozomy; Hypertension; Genotype; mužské pohlaví; potkani inbrední SHR; krysa rodu Rattus; kvantitativní znak dědičný; myokard; zvířata; Blood Pressure; mapování chromozomů; Rats, Inbred BN; Hemodynamics; potkani inbrední BN; Myocardium; hemodynamika; Chromosomes; zvířata kongenní; Chromosome Mapping; hypertenze; Rats, Inbred WKY; Animals, Congenic; Rats, Inbred SHR; potkani inbrední WKY; Male; Animals